2020
DOI: 10.1017/s0272263120000303
|View full text |Cite|
|
Sign up to set email alerts
|

The Development of a Regional Phonological Feature During a Semester Abroad in Argentina

Abstract: Although recent research suggests that gains are made in the acquisition of dialectal features during study abroad, the few studies that have been conducted on this topic in Spanish-speaking contexts have focused primarily on features characteristic of Spain. This article examines the L2 acquisition of phonological features characteristic of Buenos Aires Spanish, [ʃ] and [ʒ], known as sheísmo/zheísmo, for example the pronunciation of llave [ʝaβe] “key” as [ʃaβe] or [ʒaβe]. Participants include 23 learners of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 34 publications
4
18
1
Order By: Relevance
“…Interestingly, the students in the current study displayed a much higher adoption of this particular local dialectal form than what has been generally reported in many previous studies of other dialectal pronunciations in the study abroad context (e.g., Fox & McGory, 2007; George, 2014; Knouse, 2010; Ringer‐Hilfinger, 2012; Trimble, 2013). The results for high [ʃ ʒ] usage are, rather, more in line with the unique findings observed by Raish (2015) of high L2 adoption of Egyptian Arabic [g] and are consistent with the previous findings reported in Pozzi (2017) and Hoffman‐González (2015) for the adoption of the Argentine assibilated pre‐palatal [ʃ ʒ] features. The quick adoption of these particular regional features is noteworthy: High use of Argentine [ʃ ʒ] was observed after just 5 weeks in the current study, and as early as within 2–5 weeks in Hoffman‐González’ (2015) study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, the students in the current study displayed a much higher adoption of this particular local dialectal form than what has been generally reported in many previous studies of other dialectal pronunciations in the study abroad context (e.g., Fox & McGory, 2007; George, 2014; Knouse, 2010; Ringer‐Hilfinger, 2012; Trimble, 2013). The results for high [ʃ ʒ] usage are, rather, more in line with the unique findings observed by Raish (2015) of high L2 adoption of Egyptian Arabic [g] and are consistent with the previous findings reported in Pozzi (2017) and Hoffman‐González (2015) for the adoption of the Argentine assibilated pre‐palatal [ʃ ʒ] features. The quick adoption of these particular regional features is noteworthy: High use of Argentine [ʃ ʒ] was observed after just 5 weeks in the current study, and as early as within 2–5 weeks in Hoffman‐González’ (2015) study.…”
Section: Discussionsupporting
confidence: 91%
“…Hoffman‐González (2015) also found that two of the learners in fact decreased in their use of the dialectal sounds in free speech by the time of the exit interview (although they continued to categorically produce them in a reading task). Similarly, Pozzi (2017) found high adoption of the local [ʃ ʒ] phones by 23 American students during a semester‐long study abroad program in Buenos Aires across different production tasks (sociolinguistic interviews, word lists, reading task). The Buenos Aires variants came to be favored over non‐Buenos Aires variants, as the group increased from using the local phones only 5% of the time before or at the beginning the program to 86% by the mid‐point (2.5 months abroad) and 91% by the end (5 months abroad).…”
Section: Review Of the Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…
In the original publication of this article (Pozzi & Bayley, 2021), the phrase "word type" appears several times where the phrase "lexical item" should appear instead. These instances are in the following locations within the article: p. 117, paragraph 1, line 4 p. 119, four instances, including one in Table 3 p. 121, three instances, including one in Table 4 p. 124, paragraph 3, line 4 p. 124, paragraph 4, line 2 p. 125, paragraph 3, lines 2-3 p. 125, paragraph 4, lines 2-3 p. 127, paragraph 3, line 9 p. 127, paragraph 3, line 10Any other instances of "word type" in the article not listed above are correct as published.
…”
mentioning
confidence: 99%